極低炭素鋼冷間圧延板の剪断帯での再結晶新粒生成と再結晶挙動に及ぼす余剰Cの影響 - 船川, 義正; 辻, 知輝; 南, 秀和; 小林, 正和; 三浦, 博己 (鉄と鋼, 2019)
To investigate the effect of excess trace amounts of solute carbon on recrystallization of cold-rolled steel sheets, the recrystallization behavior of Ti-bearing ultra-low carbon steels was studied. Recrystallization was accelerated by the presence of solute carbon, and microstructure observation confirmed that recrystallized grains were generated at ferrite grain boundaries or deformation bands. In steel containing a trace amount of solute carbon, observation of many recrystallized grains generated from ferrite grain boundaries indicated that the existence of fine grains before cold-rolling of steel containing solute carbon is one cause for accelerated recrystallization.Detailed observation of recrystallized grains revealed that a large number of new recrystallized grains were generated in deformation bands in the steel containing a trace amount of solute carbon, whereas such grains were not generated in large numbers around grain boundaries in the interstitial free steel. Moreover, a fine structure was formed in the deformation bands in the steel containing a trace amount of solute carbon. These results indicated that the grain boundary migration of recrystallized grains was accelerated by high stored energy and high-angle boundaries in deformation bands.